2003
DOI: 10.1046/j.1365-2923.2003.01670.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of curricular change on medical students' knowledge of anatomy

Abstract: The introduction of the new, systems-based course has had a negative impact on medical students' knowledge of surface anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 23 publications
5
128
0
4
Order By: Relevance
“…This belief is certainly not only confined to SGUL; a pan-London study found that 87% of consultants surgeons (from seven large NHS Trusts in and around London) deemed medical students' knowledge of Anatomy to be below average, and 72% believed that junior doctors' knowledge of Anatomy was substandard (Tibrewal, 2006). These concerns are shared by others in the United Kingdom and around the world (McKeown et al, 2003;Older, 2004;Turney, 2007;Dusseau et al, 2008) The recent changes in the weighting of Anatomy within the SGUL exam- Responses to ''The weighting of Anatomy in the assessment structure discouraged me from spending time learning my Anatomy. '' statement. ination system is likely to have resulted from the institution's attempt to correct this perceived deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This belief is certainly not only confined to SGUL; a pan-London study found that 87% of consultants surgeons (from seven large NHS Trusts in and around London) deemed medical students' knowledge of Anatomy to be below average, and 72% believed that junior doctors' knowledge of Anatomy was substandard (Tibrewal, 2006). These concerns are shared by others in the United Kingdom and around the world (McKeown et al, 2003;Older, 2004;Turney, 2007;Dusseau et al, 2008) The recent changes in the weighting of Anatomy within the SGUL exam- Responses to ''The weighting of Anatomy in the assessment structure discouraged me from spending time learning my Anatomy. '' statement. ination system is likely to have resulted from the institution's attempt to correct this perceived deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the scheme of assessment changed in 2005, it was mandatory to pass each theme of the two-year preclinical course separately. This model, which does not allow for compensation, has also been called for by other academics in institutions where a system-based basic science curriculum had been introduced (McKeown et al, 2003). The themes were Basic Clinical Sciences (BCS), Community and Population Health and Personal and Professional Development (CPH-PPD), and Patient and Doctor (PD).…”
Section: Introductionmentioning
confidence: 99%
“…Accommodating such a teaching method would involve increasing staff numbers or increasing staff hours but this clearly has major resourcing issues in view of limited staff resources and time. This is not only a local issue but one that is recognized at an international level (McKeown et al, 2003;Nicholson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Developing CPD programmes is particularly pertinent within anatomical education due to its diminishing presence within broadening medical curricula [37][38][39]. Currently, numerous approaches to remedy this potential shortfall in anatomy knowledge have been proposed, including: demonstrating and teaching assistantship schemes [40], the creation of postgraduate training centres and the development of specific postgraduate anatomy qualifications, such as the Diploma in Surgical Anatomy run by the University of Dunedin in New Zealand [41].…”
Section: Introductionmentioning
confidence: 99%